Effectiveness of an optimized text message and Internet intervention for smoking cessation: A randomized controlled trial. (28th September 2021) - Graham, Amanda L.; Papandonatos, George D.; Cha, Sarah; Amato, Michael S.; Jacobs, Megan A.; Cohn, Amy M.; Abroms, Lorien C.; Whittaker, Robyn
Abstract: Aims: To evaluate the effectiveness of a combined internet and text message intervention for smoking cessation compared with an internet intervention alone. The text message intervention was optimized for engagement in an earlier multiphase optimization (MOST) screening phase. Design: A parallel, two‐group, individually randomized clinical trial (RCT) was conducted in a MOST confirming phase. Recruitment spanned December 2018 to March 2019. Follow‐up was conducted at 3 and 9 months, beginning March 2019 and ending January 2020. Setting: United States: a digital study conducted among new registrants on a free tobacco cessation website. Participants: Eligible individuals were 618 adult current smokers in the United States, age 18 years or older who signed up for text messages during website registration (67.2% female, 70.4% white). Interventions: The treatment arm (WEB+TXT; n  = 311) received access to the website and text messaging. The control arm (WEB; n  = 307) received access to the website alone. Measurements: The primary outcome was self‐reported 30‐day point prevalence abstinence (ppa) at 9 months post‐randomization analyzed under intent to treat (ITT), counting non‐responders as smoking. Secondary outcomes included 3‐month measures of 30‐day ppa, intervention engagement and intervention satisfaction. Findings: Abstinence rates at 9 months were 23.1% among WEB+TXT and 23.2% among WEB (OR = 1.00, 95% CI = 0.69–1.45; P  = 0.99). WEB+TXT increased engagement with 5 of 6 interactive features (standardized mean difference (SMD) = 0.26–0.47, all P  < 0.001) and repeat website visits (48.7% vs 38.9%, SMD = 0.14, P  = 0.02). Satisfaction metrics favored WEB+TXT (satisfied: 96.3% vs 90.5%, SMD = 0.17, P  = 0.008; recommend to friend: 95.9% vs 90.1%, SMD = 0.16, P  = 0.028). Conclusions: A randomized controlled trial found no evidence that a combined internet and text message intervention for smoking cessation compared with an internet intervention alone increased 9‐month abstinence rates among adult current smokers in the United States, despite evidence of higher levels of intervention engagement and satisfaction at 3 months.